2018
DOI: 10.1063/1.5025856
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of lonsdaleite silicon nanowires: A promising material for optoelectronic applications

Abstract: Lonsdaleite silicon has exhibited a wealth of fascinating properties and is known to have photoluminescence at room temperature. Several researchers have reported the limitations of diamond cubic silicon in the area of optoelectronic devices due to its indirect band gap. Therefore, different phases of silicon are investigated worldwide for the substitute of diamond silicon to overcome its limitation. Recently, it is suggested that lonsdaleite silicon nanowires (SiNWs) can be used as a potential material for op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 20 publications
5
24
1
Order By: Relevance
“…The formation of NWs with hexagonal crystal symmetry has attracted enormous interest among researchers. Indeed, on one hand it allows some indirect band gap materials, such as Ge and Si 1– x Ge x alloys, to feature a direct band gap, thus holding the promise for the realization of efficient and cost-effective optoelectronic Si-based devices . On the other hand, in III–V semiconductor NWs it has enabled the unprecedented possibility to switch between different crystal structures during the NW accretion, thus making crystal phase engineering a novel and powerful degree of freedom in the formation of heterostructures. , In heterostructures, the electronic and phononic properties can be modulated along the NW axis, with enormous potential for optoelectronic, photovoltaics, , and thermoelectric , applications.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of NWs with hexagonal crystal symmetry has attracted enormous interest among researchers. Indeed, on one hand it allows some indirect band gap materials, such as Ge and Si 1– x Ge x alloys, to feature a direct band gap, thus holding the promise for the realization of efficient and cost-effective optoelectronic Si-based devices . On the other hand, in III–V semiconductor NWs it has enabled the unprecedented possibility to switch between different crystal structures during the NW accretion, thus making crystal phase engineering a novel and powerful degree of freedom in the formation of heterostructures. , In heterostructures, the electronic and phononic properties can be modulated along the NW axis, with enormous potential for optoelectronic, photovoltaics, , and thermoelectric , applications.…”
Section: Resultsmentioning
confidence: 99%
“…9−15 As for the electronic and optical properties, it was shown that ultrathin 2H−Si NWs can have direct band gap and an increased optical absorption with respect to 3C−Si NWs. 9,14 The same behavior is still maintained in larger diameter NWs and can be enhanced by applying strain, opening great promises for photovoltaic applications. 10,16 Band alignment in hexagonal-cubic axial NWs was studied highlighting the possibility to switch the carrier localization by playing on the diameter.…”
mentioning
confidence: 90%
“…Driven by this evidence, many theoretical and experimental works were dedicated to the description of the main features of this novel phase NWs. As for the electronic and optical properties, it was shown that ultrathin 2H–Si NWs can have direct band gap and an increased optical absorption with respect to 3C–Si NWs. , The same behavior is still maintained in larger diameter NWs and can be enhanced by applying strain, opening great promises for photovoltaic applications. , Band alignment in hexagonal-cubic axial NWs was studied highlighting the possibility to switch the carrier localization by playing on the diameter. , On the other hand, the vibrational and thermal properties of 2H NWs were also investigated, , revealing a strongly reduced thermal conductivity with respect to 3C NWs which could be exploited in the field of thermoelectrics. , …”
mentioning
confidence: 99%
“…[140][141][142][143][144][145][146] In particular, Si-NWs showing the hexagonal-diamond (2H) phase have been the object of intense study because of their potential for adding new functionalities to 3C Si-NWs. The electronic, optical and transport properties of 2H-Si-NWs [147][148][149][150][151][152][153] have been under scrutiny, highlighting how this phase can offer a further degree of property modulation with respect to the versatility of 3C-Si-NWs. For example, it has been shown that 2H-Si-NWs are characterized by a more pronounced QC effect than 3C-Si-NWs and by a more enhanced optical absorption in the visible region.…”
Section: Hexagonal Si Nanowiresmentioning
confidence: 99%